Capital Market in Indonesia - Sarjan Sarjan; Nadya Aisya Setiawanti; Masno Marjohan (Indonesian Development of Economics and Administration Journal, 2025)
The capital market in Indonesia has experienced rapid development in recent decades, along with the increasing need for corporate funding and public interest in investment. This study aims to analyze the role of the capital market in the national economy, focusing on the mechanisms, challenges, and opportunities faced. This research uses a qualitative method based on a literature study to evaluate the dynamics of the capital market, including regulation, the role of the Indonesia Stock Exchange (IDX), and the contribution of financial technology. The analysis shows that the capital market provides efficient resource allocation, increases liquidity, and enables risk diversification. However, this market faces challenges such as low financial literacy and dependence on foreign capital. Great opportunities also arise from technological advances and the development of ESG-based financial instruments. The study concludes that increased collaboration between regulators, market participants, and the public can support the inclusiveness and growth of Indonesia's capital market.